HISTORY OF EDUCATION FOR NEGROES/AFRODESCENDENTS AND INDIGENOUS PEOPLE: A LATINOAMERICAN PERSPECTIVE - Ocoró Loango, Anny; Escalante Fernández, Carlos (Historia y Memoria de la Educación, 2024)
This article analyses the existing approaches to the history of education among Indigenous peoples and Afro-descendants in the Iberoamerican Congresses of the History of Latin American Education (Congresos Iberoamericanos de Historia de la Educación Latinoamericana, CIHELA) between 1992 and 2021. It also takes into account works which have been produced outside academic circles and conferences but have nonetheless contributed to the history of education from an ethnic or racial perspective. It seeks to address the following questions: Which are the main thematic and analytic approaches on the topic? Which are the most commonly addressed problems? Finally, it argues that the history of education among Afro-descendants and Indigenous peoples is an emergent field within CIHELA because no continuous tradition of study of this topic has developed and few countries have an uninterrupted production on the subject.